Governance-Risk Decoupling: Operational Risk Management, Board Independence, and Operational Resilience in Ghanaian Banks: An EmergingMarket Perspective - Patrick Boamah; Richmell Baaba Amanamah; Rabiatu Kamil (Journal Management & Economics Review (JUMPER), 2026)
In an era of economic shocks, digital disruptions, and escalating systemic risks, operational resilience has become a critical determinant of stability and trust in the banking system. This study investigates the key drivers of operational resilience in Ghanaian commercial banks, an emerging-market context where governance models may differ from Western norms. The research employs an exploratory sequential mixed-methods design. Initial qualitative phase involved in-depth interviews with ten senior risk and governance experts, analyzed via thematic analysis. The subsequent quantitative phase surveyed 384 banking professionals. Covariance-based structural equation modeling (SEM), incorporating an integrated interaction term, was used to test relationships. Strong Operational Risk Management (ORM) emerges as the most powerful driver of operational resilience. Board Independence shows only a modest direct positive effect. Notably, higher board independence slightly weakens the positive impact of ORM on resilience (significant negative interaction), indicating governance–risk decoupling. In this context, genuine resilience stems primarily from deep operational capabilities rather than formally independent boards; ceremonial adoption of independence, disconnected from day-to-day risk processes, can subtly undermine resilience. Drawing on the Resource-Based View, Risk Governance Theory, and Institutional Theory, this paper provides evidence-based insights into why Western-style board independence may not translate effectively to emerging financial systems like Ghana's. It challenges the universal application of such governance models and highlights the primacy of embedded operational risk capabilities for true resilience, offering practical implications for regulators, bank leaders, and governance reformers in developing economies.